Stepwise and independent origins of roots among land plants - Hetherington, A; Dolan, L (Nature Publishing Group, 2018)
Roots are one of the three fundamental organ systems of vascular plants1, where they play roles in anchorage, symbiosis, nutrient and water uptake2–4. However, the fragmentary nature of the fossil record obscures their origins and makes it difficult to identify the sole defining characteristic of extant roots – the presence of self-renewing structures called root meristems covered by a root cap at their apex1–9. Here we report the discovery of the oldest meristems of rooting axes preserved in the 407 million year old Rhynie chert, the earliest preserved terrestrial ecosystem10. These meristems, of the lycopsid Asteroxylon mackiei11–14, lacked root caps and instead developed a continuous epidermis over the surface of the meristem. A. mackiei rooting axes and meristems are therefore unique among vascular plants. These data support the hypothesis that roots, as defined in extant vascular plants by the presence of a root cap7, were a late innovation in the vascular lineage. Roots therefore acquired traits in a stepwise fashion. The relatively late origin of roots with caps in lycophytes is consistent with the hypothesis that roots evolved multiple times2, rather than having a single origin1, and the extensive similarities between lycophyte and euphyllophyte roots15–18 therefore represent examples of convergent evolution. The key phylogenetic position of A. mackiei, with its transitional rooting organ, between early diverging land plants that lacked roots and the derived plants that developed roots, demonstrates how roots were “assembled” during the course of plant evolution.